2009
DOI: 10.1007/s00125-009-1507-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of left ventricular function by lifestyle intervention in obesity: contributions of weight loss and reduced insulin resistance

Abstract: Aims/hypothesis Weight excess and insulin resistance mediate the link between obesity and left ventricular dysfunction. We investigated the effect and mechanisms of lifestyle modification on left ventricular function changes in obese patients. Methods Reduction of body weight and insulin resistance was sought using a behavioural intervention programme including dietary restrictions and exercise training in 261 patients (age 45±13 years) with BMI ≥30 kg/m 2 , no history of cardiac disease and a normal stress ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…We did not have a group of patients who achieved weight loss without any reduction in HbA1c levels to examine the independent contribution of weight loss alone without improved glycaemic control on LV function. However, as the study by Kosmala et al has shown [32], improvement in LV function with weight loss alone (their patients did not have significant reduction in HbA1c with behavioural intervention) was less frequently observed in patients with diabetes. We did not evaluate changes in insulin resistance in our patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We did not have a group of patients who achieved weight loss without any reduction in HbA1c levels to examine the independent contribution of weight loss alone without improved glycaemic control on LV function. However, as the study by Kosmala et al has shown [32], improvement in LV function with weight loss alone (their patients did not have significant reduction in HbA1c with behavioural intervention) was less frequently observed in patients with diabetes. We did not evaluate changes in insulin resistance in our patients.…”
Section: Discussionmentioning
confidence: 87%
“…In a study of 261 patients with BMI ≥ 30 kg/m 2 who undertook a behavioural intervention programme including dietary restriction and exercise training, independent predictors of improvement in LV function were weight reduction, improvement in insulin resistance and absence of diabetes [32]. There was no significant reduction in HbA1c levels with intervention in either the adherent group or in the non-adherent group; therefore, the effects of improved glycaemic control on LV function was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the respective study designs for exercise in obese type-2 diabetics have maintained the traditional low-fat/high-carbohydrate nutrition [87,88]. Their ambiguous outcome fits the results of the low-fat vs. GL restriction dietary arm in spite of moderate aerobic training as discussed above [30••].…”
Section: Exercise Trainingmentioning
confidence: 89%
“…Intentional weight loss in subjects who achieve reductions of 5% to 10% body weight using combinations of behavioral weight loss, dietary, and exercise interventions have shown significant reductions in LV hypertrophy, characterized by decreases in LV mass and wall thickness [17, 33•, 58, 65, 66]. Similarly, weight loss significantly improves LV systolic and diastolic function in obese subjects [17,65,67,68]. Improvements in LV diastolic and systolic function are characterized by echocardiographic load-independent indices of systolic and diastolic myocardial velocities at the mitral annulus and transmitral flow velocities, measures that demonstrate improved LV relaxation and decreased LV filling pressures.…”
Section: Effects Of Weight Loss On Left Ventricular Function and Chromentioning
confidence: 97%
“…Improvements in LV diastolic and systolic function are characterized by echocardiographic load-independent indices of systolic and diastolic myocardial velocities at the mitral annulus and transmitral flow velocities, measures that demonstrate improved LV relaxation and decreased LV filling pressures. In a study of 261 obese subjects with no CHD enrolled in a lifestyle intervention with dietary restrictions and exercise for 6 months, there were significant improvements in LV systolic and diastolic function and peak ventilatory exercise capacity among those who achieved 5% weight loss and a 20% decrease in the homeostasis model assessment of insulin resistance (HOMA) index [68]. These improvements in LV function were less predictable in T2DM, suggesting that insulin resistance and T2DM may have independent deleterious effects on LV dysfunction.…”
Section: Effects Of Weight Loss On Left Ventricular Function and Chromentioning
confidence: 98%